MODERN POLICY OF ATTRACTING FOREIGN INVESTMENT: GLOBAL EXPERIENCE AND NATIONAL DIMENSION - Yuliia Poliakova; Oksana Protsevyat (ДУ «Інститут регіональних досліджень імені М. І. Долішнього НАН України»., 2025)
The article examines the features of the formation and implementation of modern foreign investment attraction policies in global practice and their projection for the domestic economy. It emphasizes that countries around the world successfully implement mechanisms aimed at ensuring the transparency of investment resources, protecting national economies from risky foreign investments, and gaining advantages from the inflow of foreign investments. The article examines various types of foreign direct investment (FDI), including vertical, horizontal, conglomerate, greenfield, and brownfield investments. Current trends and dynamics of attracting foreign direct investments in different regions of the world are analyzed. The global experience in developing the principles and foundations of policies and efforts aimed at attracting and promoting foreign direct investments, as well as maximizing the effectiveness of FDI attraction measures — particularly in the context of achieving sustainable development goals — is explored. The impact of foreign direct investment inflows on the economic development indicators of countries with the largest GDP volumes is assessed. The article reveals that an increase in foreign direct investment by 1 million USD directly leads to a 68 million USD increase in GDP in leading countries. The principles of OECD investment policy formation and the experience of OECD countries in supporting governments in the process of attracting foreign investment are considered. Priority directions for expanding opportunities related to foreign direct investment for Ukraine during the post-war reconstruction period, which will require significant investment, are substantiated. The article argues that the study and adaptation of foreign experience, providing institutional support for the implementation of investment projects, introducing investment insurance mechanisms, and promoting successful projects should be Ukraine’s priority.
СУЧАСНА ПОЛІТИКА ЗАЛУЧЕННЯ ІНОЗЕМНИХ ІНВЕСТИЦІЙ: СВІТОВИЙ ДОСВІД ТА НАЦІОНАЛЬНИЙ ВИМІР
Keywords: foreign investment; foreign direct investment; investment policy; institutional support; sustainable development